2014
DOI: 10.1007/s10096-014-2102-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States

Abstract: Bacterial meningitis is an important source of mortality and morbidity worldwide. Data exist on specific vaccines against Streptococcus pneumoniae and Neisseria meningitidis indicating that they reduce the incidence of meningitis, yet comprehensive information on the trend of bacterial meningitis is still lacking. We analysed the Kids' Inpatient Database and the National Inpatient Database considering all bacterial meningitides in the United States, excluding cases of tuberculosis and sexually transmitted dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…1,14,37 Hib and PCV-13 vaccines are already available for infants starting from two months of age in the Turkish NIP and the meningococcal vaccine for Hajj pilgrims has already been switched to conjugated quadrivalent vaccine in order to decrease carriage of the microorganism by returning pilgrims. In this study we observed a drastic decreased of Hib meningitis in Turkish children since Hib vaccine has been introduced in NIP.…”
Section: Discussionmentioning
confidence: 99%
“…1,14,37 Hib and PCV-13 vaccines are already available for infants starting from two months of age in the Turkish NIP and the meningococcal vaccine for Hajj pilgrims has already been switched to conjugated quadrivalent vaccine in order to decrease carriage of the microorganism by returning pilgrims. In this study we observed a drastic decreased of Hib meningitis in Turkish children since Hib vaccine has been introduced in NIP.…”
Section: Discussionmentioning
confidence: 99%
“…The results generated by these interventions on human health and longevity changed profoundly the historical relationship between infectious diseases and human race [2][3][4]. The eradication of smallpox and the large reduction of cases of poliomyelitis and measles are some examples of the beneficial impact of immunisation programmes [2,3].…”
Section: Introductionmentioning
confidence: 98%
“…Meningitis caused by Staphylococcus aureus differs from other bacterial meningitis in its pathogenesis, usually occurring following postneurosurgical procedure or head trauma. From 1997 to 2011, the incidence of pneumococcal and meningococcal meningitis declined by 8 and 6%, respectively [6]. In a report from 1998 to 2007 in the USA, S. pneumoniae accounted for 58% of the cases, followed by group B Streptococcus (GBS) (18.1%), N. meningitidis (13.9%) and H. influenzae (6.7%) [7].…”
Section: Epidemiological Consideration For Treatment Strategies For Cmentioning
confidence: 99%
“…Initial treatment of suspected bacterial meningitis 6.1 Empiric treatment of suspected bacterial meningitis Bacterial meningitis needs prompt antibiotics administration. Empirical antibiotics should not be delayed either by lumbar puncture or by CT ( Table 6).…”
Section: Consideration Of Vaccinationsmentioning
confidence: 99%
See 1 more Smart Citation